Factors influencing implementation of Islamic will among rural muslim community in Sungai Acheh - Aufa Najiha, Mohd Foad (2018)
This study intends to explore on the factors influencing the failure of managing family's wealth among Muslim community through the method of Islamic will. 350 sets of questionnaire have been distributed to the Muslim community in kampung Sungai Acheh. Lack of knowledge on Islamic will, low Islamic spiritual intelligence and challenging barriers in performing Islamic will are assumed as among of the factors that lead failure. The result reveals that Islamic spiritual intelligence and barriers influence the implementation of Islamic while knowledge does not. In conclusion, Islamic spiritual intelligence and barriers contribute to the implementation of Islamic will among Muslim community in Sungai Acheh. There could be other probable factors which are not included in this study.